2021
DOI: 10.1038/s41598-021-94169-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the canonical Wnt signaling pathway by a β-catenin/CBP inhibitor prevents heart failure by ameliorating cardiac hypertrophy and fibrosis

Abstract: In heart failure (HF) caused by hypertension, the myocyte size increases, and the cardiac wall thickens. A low-molecular-weight compound called ICG001 impedes β-catenin-mediated gene transcription, thereby protecting both the heart and kidney. However, the HF-preventive mechanisms of ICG001 remain unclear. Hence, we investigated how ICG001 can prevent cardiac hypertrophy and fibrosis induced by transverse aortic constriction (TAC). Four weeks after TAC, ICG001 attenuated cardiac hypertrophy and fibrosis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…This finding indicated that inhibition of Ang II-induced Wnt activation was related to KDM5B knockdown. In recent years, increasing studies have demonstrated that the Wnt-related pathway contributed to tissue fibrosis and worked together with the TGF-β pathway. , Therefore, we focused on the Wnt-related pathway in the following study.…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicated that inhibition of Ang II-induced Wnt activation was related to KDM5B knockdown. In recent years, increasing studies have demonstrated that the Wnt-related pathway contributed to tissue fibrosis and worked together with the TGF-β pathway. , Therefore, we focused on the Wnt-related pathway in the following study.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that up-regulated miR-128 mediated heart injury by activating wnt signaling pathway in HF mice [28]. Another study showed that inhibition of the canonical wnt signaling pathway prevents HF by ameliorating cardiac hypertrophy and brosis [29]. And transcription factor 7-like 2 mediates canonical Wnt/β-catenin signaling in HF [30].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent activation of endothelial Wnt/β-catenin signaling induces HF ( 30 ). Besides, cardiac fibroblasts are the main cell types in cardiac fibrosis ( 31 ); interestingly, Wnt/β-catenin signaling also had vital functions in regulating fibroblast activation and ECM gene expressions ( 32 ). Thus, studying the Wnt/β-catenin pathway is the key to unveiling the pathogenesis in HF.…”
Section: Discussionmentioning
confidence: 99%